Production functions with given elasticities of output and production - Khatskevich, Guennadi A.; Pranevich, Andrei F. (Journal of the Belarusian State University. Economics, 2019)
In this paper we consider inverse problems of identifying multifactor production functions from given elasticity of output or from given elasticity of production. The analytical forms of multifactor production functions with given elasticity of output or with given elasticity of production are indicated. Classes of twofactor production functions that correspond to given (constant, linear, linearfractional, exponential, etc.) elasticity of output with respect to capital (elasticity of output with respect to labour) are obtained. The set of twofactor production functions with given (constant, linear, linearfractional, exponential, etc.) elasticity of production is built. The obtained results can be applied in modeling of production processes.
Keywords: production function; inverse problem; output elasticity; elasticity of production